MANAJEMEN DIRI GURU RAUDHATUL ATHFAL (RA) BERPRESTASI DI YOGYAKARTA - Noor, Fu`ad Arif (Pascasarjana IAIN Kudus, 2019)
This study was conducted to determine the self-management of outstanding RA teachers in Yogyakarta who are able to be role models. Qualitative research methods with psychological approaches are carried out directly to the object under study, in order to obtain all data relating to the self-management of high achieving RA teachers. Analysis techniques reduce data, present, draw conclusions and verify data. Data collection uses interviews, documentation, and observation, and tests the validity of the data with triangulation credibility.The results revealed that: self-management of outstanding RA teachers in Yogyakarta principally increased efficiently, were effective in work productivity, and functioned to foster self-character and competence to change better and become habituated to daily routines, as well as the influence of self-development on the performance of outstanding RA teachers in Yogyakarta is able to provide strength and produce a work ethic called hard work, and smart work, and sincere work that can foster positive, productive, and contributive behavior.